Unclock Your Home’s Security: Bisnis Plan Smart Key System Kayu Minimalist Dengan Layar Notifikasi Dan Lampu Ambient - Keisha AlMisky Putri Raindra; Alvi Nur Rahma; Raden Syahid Prabowo Riyadi (Komunika : Jurnal Ilmiah Komunikasi, 2025)
People often forget important items such as wallets, ID cards, umbrellas, and especially house, office, or vehicle keys. We designed this product to alleviate people's anxiety, because losing keys wastes their time searching for them in the wrong places, especially when they are in a hurry. We believe that people need help with the product we are launching, to make it easier for them and remind them not to store their keys anywhere. This product is a rectangular wooden board that is mounted on the wall, which functions as a key storage and notification hub. Above the board are five cylindrical wooden key hooks, all of which have magnets and are surrounded by warm yellow ambient light, indicating the integration of technology or sensors when the keys are not attached or empty. On the right end of the board is a small digital screen that displays notifications or information. The design, dominated by natural wood textures and clean lines, is in perfect harmony with the concept of a modern and minimalist home. By increasing efficiency, we can reduce the time spent looking for misplaced items. And with our efforts to ensure peace of mind for users, they will never have to leave their important items lying around again. This product is designed to be premium and looks attractive to a market segment that currently uses smart home technology.